Penerapan Sistem Informasi Akuntansi Atas Penyertaan Modal Pemerintah Yang Bersumber Dari Penghapusan Piutang Negara Menjadi Hibah Penyertaan Modal Serta Pengalihan Aset Tetap Milik Pemerintah Kepada Perusahaan Daerah Air Minum Tirta Raya Kabupaten Kubu Raya - B2092162008, RIZKY ADITHYA (MAKSI UNTAN, 2019)
This research aims to explain the accounting treatment for government capital participation derived from the transfer of ownership of state-owned fixed assets based on Kubu Raya Regional Regulation Number 5 of 2013. The research method used in thie research is a descriptive method with qualitative approach. The data collection tools used were observation, interviews and documentation.The result of this research shows that capital participation made by the central government indicates inconsistency between the minutes of the handover and the recognition of grant capital that should be presented in the financial statement of PDAM Tirta Raya of Kubu Raya by referring to Government Regulation Number 27 of 2014 concerning Management of State/ Regional Property. While equity participation derived from the PDAM debt write-off converted into non-cash grant of regional capital investment was performed by reconciling the loan with Direcctorate General of Treasury of West Kalimantan Province related to the amount of cut-off date loans. The reconciliation result of the cut-off date is subsequently written off and converted into government equity by referring to the Minister of Home Affairs Regulation Number 48 of 2016.